2014
DOI: 10.1128/aem.01532-14
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Comparison of Cultivable Norovirus Surrogates in Response to Different Inactivation and Disinfection Treatments

Abstract: g Human norovirus is the leading cause of epidemic and sporadic acute gastroenteritis. Since no cell culture method for human norovirus exists, cultivable surrogate viruses (CSV), including feline calicivirus (FCV), murine norovirus (MNV), porcine enteric calicivirus (PEC), and Tulane virus (TuV), have been used to study responses to inactivation and disinfection methods. We compared the levels of reduction in infectivities of CSV and Aichi virus (AiV) after exposure to extreme pHs, 56°C heating, alcohols, chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
174
3
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 172 publications
(204 citation statements)
references
References 67 publications
20
174
3
3
Order By: Relevance
“…The short contact time used in previous studies (< 5 min) could explain the absence of any significant effect of alcohol (D'Souza and Su 2010) and of chlorhexidine (Park et al 2010;Iwasawa et al 2012;Matsuhira et al 2012) on the infectious titre of MNV and FCV. Our results as well as previous studies confirmed that MNV is more susceptible to alcohol and chlorhexidine than FCV (Park et al 2010;Tung et al 2013;Cromeans et al 2014). These data also suggest differences between MNV and FCV regarding viral capsid integrity (Cannon et al 2006;Park et al 2010).…”
Section: Discussionsupporting
confidence: 91%
“…The short contact time used in previous studies (< 5 min) could explain the absence of any significant effect of alcohol (D'Souza and Su 2010) and of chlorhexidine (Park et al 2010;Iwasawa et al 2012;Matsuhira et al 2012) on the infectious titre of MNV and FCV. Our results as well as previous studies confirmed that MNV is more susceptible to alcohol and chlorhexidine than FCV (Park et al 2010;Tung et al 2013;Cromeans et al 2014). These data also suggest differences between MNV and FCV regarding viral capsid integrity (Cannon et al 2006;Park et al 2010).…”
Section: Discussionsupporting
confidence: 91%
“…First, the detection of viral RNA does not necessarily indicate the presence of infectious NVGII. However, given that human noroviruses are not currently cultivable, 35 research to determine infectious prevalence would need to be undertaken with a surrogate calicivirus 36 and, as such, may also not accurately reflect the prevalence of infectious norovirus on mothers' hands. Second, this study only represents a cross-sectional comparison of NVGII hand contamination during the rainy versus the dry season.…”
Section: Discussionmentioning
confidence: 99%
“…While the use of human subjects is clearly optimal for at least certain areas of human NoV research, it has its own limitations including the time-consuming and highly regulated processes associated with human subject research, the unknown preexposure history of the volunteers, the restricted sampling procedures, the associated cost and facilities, and the lack of cell culture system for the analysis of clinical samples. (Cromeans et al, 2014;Wang et al, 2013). However, the major value of the ReCV/macaque model over the other surrogate models is its human NoV-like diversity and this point should not be ignored.…”
Section: Closing Remarksmentioning
confidence: 99%